Über Klima und Wasserhaushalt des Altiplano (Bolivien, Peru) während des Hochstandes der letzten Vereisung - Kessler, Albrecht (ERDKUNDE, 1963)
The snow line of the section of the Andes between 14° and 22° southern latitude lay about 700 m. below its pre sent height during the climax of the last glaciation. Simultaneously the surface of Lake Titicaca was larger than today and within the confines of the southern Altiplano there existed a large terminal lake - the Lago Minchin - which embraced the present Lake Poopo and the Salars of Coipassa and Uyuni. Starting from the present climatic conditions at the snow line and the altitudinal gradient of the air temperature near the ground the paper discusses the different values of the climatic elements which resulted in the depression of the snow line during the ice age. The results are checked by means of the water balance equation of the glacial Lago Minchin. Taking the minimum conditions for the existence of the Lago Minchin as derived from the present hydrological conditions of the Altiplano, the most likely solution appears to be as follows: During the climax of the last glaciation the mean annual temperature was at least 6° C lower than today whereas precipitation, or rather relative humidity, was higher. The assumption of a lesser lowering of temperature combined with even higher amounts of precipitation, or conversely, an even larger temperature depression without any increase of precipitation, explains the glacial phenomena in their total effects less satisfactorily.